KUALITAS LAYANAN PERPUSTAKAAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN DAERAH KOTA TOMOHON - Nangka, Clarisa Ignasia Rachelle; Kawung, Evelin J. R.; Tampongangoy, Deysi (Sam Ratulangi University, 2022)
This study aims to determine the quality of library services at the Regional Archives and Libraries Office of Tomohon City. The research was carried out at the Regional Archives and Library Office of Tomohon City from October to December 2021. The method used in this study was a qualitative method with informants taken using purposive sampling technique with a focus on research using service quality aspects consisting of reliability, assurance, responsiveness and tangibles. The data used are sourced from primary data and secondary data collected through interview, observation and documentation techniques. Data analysis used steps of data reduction, data presentation, and drawing conclusions. The results showed that the overall service quality of the Tomohon City regional library was very lacking, this was caused by the unavailability of competent librarians in the library so that at the time of a visit no one could explain for sure about the library or the information needed and the services provided in terms of infrastructure. namely the need for renewable books not available in the library.